2010
DOI: 10.1007/s11165-010-9172-7
|View full text |Cite
|
Sign up to set email alerts
|

Coteaching and Disturbances: Building a Better System for Learning to Teach Science

Abstract: Science education research has examined the benefits of coteaching for learning to teach in elementary and secondary school contexts where coteachers bring variable levels of experience to the work of coteaching. Coteaching as a pedagogical strategy is being implemented at the university level but with limited research. Drawing from the field of activity theory and our emic experience as coteachers, we examine the enactment of coteaching in university science education courses. One of the tools central to our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 32 publications
0
11
0
2
Order By: Relevance
“…Beck, 2006;Shibley, 2006). In the study by Milne et al (2011) and in this study, the interest is in the way two (or potentially more) activity systems representing different disciplinary areas interact through team teaching to achieve an outcome. Taking the teacher training programme as the activity system and the preparation of science teachers as the object of the activity system, they found that co-teaching offers the possibility of making "disturbances" (indicating tensions/contradictions) to the preparation of science teachers that have the potential to transform the activity in which the co-teachers are engaged.…”
Section: Integrating Lln In Vetmentioning
confidence: 98%
See 2 more Smart Citations
“…Beck, 2006;Shibley, 2006). In the study by Milne et al (2011) and in this study, the interest is in the way two (or potentially more) activity systems representing different disciplinary areas interact through team teaching to achieve an outcome. Taking the teacher training programme as the activity system and the preparation of science teachers as the object of the activity system, they found that co-teaching offers the possibility of making "disturbances" (indicating tensions/contradictions) to the preparation of science teachers that have the potential to transform the activity in which the co-teachers are engaged.…”
Section: Integrating Lln In Vetmentioning
confidence: 98%
“…led to colleagues learning from and motivating each other (e.g. Milne et al (2011) draw on the ideas of Engeström's theory of expansive learning, the third generation of cultural-historical activity theory (CHAT) that has its roots in Vygotsky's sociocultural theory of human development (Engeström, 1987(Engeström, , 2001. Recent work by Milne, Scantlebury, Blonstein, and Gleason (2011) employed activity theory as a tool to examine the conceptually similar "co-teaching" in a teacher training context.…”
Section: Integrating Lln In Vetmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, a model of teacher education was used that originally had been implemented and studied at the University of Philadelphia: {coteaching | cogenerative dialoguing} (Tobin & Roth, 2006) and then adapted, in whole or part, to other settings and countries (e.g., Milne, Scantlebury, Blonstein, & Gleason, 2011;Murphy, Carlisle, & Beggs, 2009;Roth & Tobin, 2005). The {coteaching | cogenerative dialoguing} model had been proposed as an explicit attempt to overcome the theory-practice gap in teacher education and teacher development (Roth, Lawless, & Tobin, 2000).…”
Section: {Coteaching | Cogenerative Dialoguing} As Context For Teachimentioning
confidence: 99%
“…Coteaching is successful because it increases access to social and material resources, and thereby increases opportunities for actions that otherwise would not occur and that greater teaching opportunities provide newcomers with greater opportunities of learning to teach (Roth, Masciotra, & Boyd, 1999;Stith & Roth, 2010;Tobin, Zurbano, Ford, & Carambo, 2003;Wassell & Lavan, 2009). Moreover, coteaching expands opportunities for the evolution of the activity system of preparing teachers and it plays an important role in identifying disturbances and theorizing underlying contradictions within this system (Milne, Scantlebury, Blonstein, & Gleason, 2011). Although there are other collaborative models of teaching, coteaching differs from others in that it emphasizes full, joint responsibility for all aspects of teaching rather than a division of labor.…”
Section: Coteachingmentioning
confidence: 99%